PENGEMBANGAN TES DIAGNOSTIK PADA MATERI SUHU DAN KALOR DI SMA - Husnaini, Gina; Sutrisno, Leo; TMS, Haratua (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to produce a good diagnostic test in heat and temperature to diagnose students misconception. This study is categorized as a research development. The initial draft result obtained 24 questions that have been validated by four physics lecturers and one physics teacher. The questions was tested on a small scale with 36 students of class XII in SMA Negeri 7 Pontianak. This test is to find out the reliability value and difficulty?s level of the test. The results of this experiment obtained reliability value is 0.48. The large-scale trials was conducted at SMA Negeri 2 Pontianak and SMA Negeri 8 Pontianak with a sample of 128 students. The results showed, as many as 16 questions of diagnostic tests of heat and temperature classified as an expected diagnostic test criteria. This is indicated by validator which validity of the content is 0,78: reliability value is 0.65: legibility?s level is 3,78: and difficulty?s level is medium-easy. As a result, the development of this diagnostic test has the potential to serve as a diagnostic test instrument for uncovering misconceptions in heat and temperature.Keywords: diagnostics test, misconception, heat and temperature